2021
DOI: 10.1186/s12889-021-11803-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of a recommender system for selecting optimal messages for smoking cessation: patterns and effects of user-system engagement

Abstract: Background Motivational messaging is a frequently used digital intervention to promote positive health behavior changes, including smoking cessation. Typically, motivational messaging systems have not actively sought feedback on each message, preventing a closer examination of the user-system engagement. This study assessed the granular user-system engagement around a recommender system (a new system that actively sought user feedback on each message to improve message selection) for promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The analyses on the association between intervention engagement (ie, the number of logins, self-monitoring registrations, and exercises) and the outcome did not yield any significant effects. This study showed the overall prevailing pattern of the majority of participants quitting the use of the intervention in the first few days and a smaller group that uses the intervention for a longer period [ 40 ]. However, other studies on digital SC interventions have shown a dose-response relationship between intervention engagement and outcome [ 9 , 10 , 41 ], with higher engagement predicting greater SC rates, although this is sometimes limited to certain engagement measures [ 34 ] or with low quality of the evidence due to low follow-up rates [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analyses on the association between intervention engagement (ie, the number of logins, self-monitoring registrations, and exercises) and the outcome did not yield any significant effects. This study showed the overall prevailing pattern of the majority of participants quitting the use of the intervention in the first few days and a smaller group that uses the intervention for a longer period [ 40 ]. However, other studies on digital SC interventions have shown a dose-response relationship between intervention engagement and outcome [ 9 , 10 , 41 ], with higher engagement predicting greater SC rates, although this is sometimes limited to certain engagement measures [ 34 ] or with low quality of the evidence due to low follow-up rates [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sadasivam et al, (2016) examined a “hybrid machine learning recommender system that selects and sends motivational messages using algorithms that learn from message ratings”, finding that compared to standard computer-tailored health communication (CTHC), the recommender system outperformed CTHC on measures related to self-perceived influence to quit, yet did not result in improved smoking cessation rates [ 46 ]. Similarly, Chen et al (2021) analyzed smoking cessation using a recommender-based motivational messaging intervention and found high user engagement predicted 6-month smoking cessation [ 47 ]. However, these studies were excluded from the present review for their study design because they did not utilize machine learning to evaluate smoking cessation outcomes, rather the intervention utilized machine learning.…”
Section: Discussionmentioning
confidence: 99%
“…In the cognitive-behavioral model of relapse prevention, for instance, affective states and cognitive processes like self-efficacy and motivation have long been identified as drivers of relapse in substance use disorders [31][32][33][34]. Delay discounting is also strongly associated with smoking outcomes, differentiating smokers from controls [35][36][37][38][39][40], forecasting the intensity of use [36,[41][42][43], and predicting treatment outcomes [44,45]. While several biomarkers for quitting smoking (such as cotinine and carbon monoxide) [22] have been discovered using non-machine learning techniques, machine learning has helped to uncover a brand-new biomarker in fMRI resting-state activity [10].…”
Section: Discussionmentioning
confidence: 99%